Pengelolaan Self-disclosure Generasi Z melalui Penggunaan Multiple Accounts di Instagram - Tandres, Herliany; Winduwati, Septia (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
This research extensively explores the phenomenon of Self-disclosure among Generation Z in the context of using Multiple Accounts on the Instagram platform, aiming to gain a deeper understanding of how Generation Z carefully manages their self-disclosure. Within the theoretical framework of Self-disclosure theory and the Johari Window, a qualitative constructivist phenomenological approach is applied, focusing on individuals from Generation Z who actively use more than two Instagram accounts. The research findings indicate that Generation Z consciously categorizes their accounts into three separate categories: a personal account for general content, a private account for more profound self-disclosure to trusted followers, and a professional account for specialized content showcasing their expertise. These findings reflect Generation Z's early awareness of the importance of shaping and maintaining their personal branding and digital identity through tailored openness based on the type of account they manage. This research provides deeper insights into how Generation Z manages Multiple Accounts, and these implications can be used to understand their digital self-disclosure dynamics in this modern era. Penelitian ini secara rinci mengeksplorasi fenomena Self-disclosure Generasi Z dalam konteks penggunaan Multiple Accounts di platform Instagram, bertujuan untuk memahami secara lebih mendalam bagaimana Generasi Z secara hati-hati mengelola pengungkapan diri mereka. Dalam kerangka teoretis teori Self-disclosure dan Johari Window, pendekatan kualitatif fenomenologi konstruktivisme diterapkan dengan fokus pada individu Generasi Z yang aktif menggunakan lebih dari dua akun Instagram. Hasil penelitian menunjukkan bahwa Generasi Z dengan sadar mengelompokkan akun mereka menjadi tiga kategori yang terpisah, akun personal untuk konten umum, akun privat untuk pengungkapan yang lebih mendalam kepada followers terpercaya, dan akun profesional untuk konten khusus yang menunjukkan keahlian mereka. Temuan ini mencerminkan kesadaran dini Generasi Z akan pentingnya membentuk dan merawat personal branding serta identitas digital mereka melalui keterbukaan yang disesuaikan dengan jenis akun yang mereka kelola. Penelitian ini memberikan wawasan yang lebih mendalam tentang bagaimana Generasi Z dalam mengelola Multiple Accounts, dan implikasi ini dapat digunakan untuk memahami dinamika pengungkapan diri mereka secara digital dalam era modern ini.